Assessing land-use impacts by clean vehicle systems - Pontau, Patricia (Animo Repository, 2015)
Transition of the current gasoline-based transportation system into a renewable fuel-based clean vehicle system has the potential to reduce greenhouse gas emissions and improve national energy security. However, the realized net environmental benefit or energy security improvement is tightly linked to the electricity fuel mix (for electric cars and plug-in hybrids) and fueling strategy (for cars using alternative liquid fuels). In addition, different types of transportation fuels have significantly different demands on land resources, both on land type and quantity. For example, biofuel production requires large quantities of agricultural land, while wind farms require land with sufficient wind density. Furthermore, there is substantial regional variation in the quality of necessary resources. Regions with higher wind speeds require less land to produce the same amount of electricity than those with lower wind speed, assuming the same turbine design. Similarly, regions with optimal soil conditions and climate for crop cultivation require less land to produce the same amount of biofuel. To enable comparison of land demand among different fuel choices for clean vehicles, this research provides a county-scale assessment of land demand based on a "per-vehicle-mile-traveled" basis. Potential clean vehicle fuels assessed in this study include ethanol produced from different feedstocks (corn and switchgrass), biodiesel from algae cultivated in open ponds and closed systems, and electricity produced from renewable sources (wind and solar). Our results show that, in general, engineered systems (wind electricity, solar electricity, and biodiesel from closed-system algae) are more land efficient than natural systems (corn ethanol from corn starch and stover, switchgrass ethanol, and biodiesel from open-pond algae). Solar electricity is the dominant regional optimal fuel choice from the land-use perspective for engineered systems while lowland switchgrass ethanol and biodiesel from open-pond algae are the major optimal choices for the natural systems. These results shed light on developing both federal and state level policies to minimize land-use impact for the development of a clean vehicle system. © 2014 Elsevier B.V. All rights reserved.